2018
DOI: 10.1175/jcli-d-17-0530.1
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal Fluctuation of the Wintertime Arctic Oscillation Pattern and Its Implication

Abstract: The multidecadal fluctuations in the patterns and teleconnections of the winter mean Arctic Oscillation (AO) are investigated based on observational and reanalysis datasets. Results show that the Atlantic center of the AO pattern remains unchanged throughout the period 1920–2010, whereas the Pacific center of the AO is strong during 1920–59 and 1986–2010 and weak during 1960–85. Consequently, the link between the AO and the surface air temperature over western North America is strong during 1920–59 and 1986–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 42 publications
(64 reference statements)
0
32
0
Order By: Relevance
“…Thus, a reasonable projection of the multidecadal changes of AO should be helpful to predict a more realistic SAT change in the NEA on the time scale of 30-50 years. Previous studies show that the circulation and SAT variations in the SEA are less affected by AO (e.g., Gong et al, 2017;Gong, Wang, Chen, & Nath, 2018;Gong, Wang, Zhou, et al, 2018;He et al, 2017), and thus, the reasons for decreasing SLP trend and corresponding increasing SAT in the SEA including the TP need to be further investigated in future studies. It is noted that the time period analyzed in this study is 40 years, and thus, to what extent internal variability contributes to the SAT trend in East Asia in a longer or shorter time scale should be further investigated in the future.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Thus, a reasonable projection of the multidecadal changes of AO should be helpful to predict a more realistic SAT change in the NEA on the time scale of 30-50 years. Previous studies show that the circulation and SAT variations in the SEA are less affected by AO (e.g., Gong et al, 2017;Gong, Wang, Chen, & Nath, 2018;Gong, Wang, Zhou, et al, 2018;He et al, 2017), and thus, the reasons for decreasing SLP trend and corresponding increasing SAT in the SEA including the TP need to be further investigated in future studies. It is noted that the time period analyzed in this study is 40 years, and thus, to what extent internal variability contributes to the SAT trend in East Asia in a longer or shorter time scale should be further investigated in the future.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Although many studies have reported that the AO can influence regional temperature, these influences may not be stable [25][26][27][28][29][30]. For example, Li et al [26] found that the link between the winter AO and an East Asian winter monsoon index experienced a significant interdecadal change during past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the North Pacific circulation variability may play a role in the intensity of the Kuroshio anticyclone. Previous studies have pointed out that the Aleutian Low (AL) is the dominant variability of atmospheric circulation over the North Pacific, which has a potential connection with the atmospheric circulation variability over other midlatitude regions [26,35,36]. Therefore, we tried to understand whether the AL can modulate the influence of ENSO on the circulation variability over the Kuroshio Extension region.…”
Section: Resultsmentioning
confidence: 99%